Between landscapes, the construction of poetics - Dala Bernardina, Jovani; Rodrigues, Hugo Bernardino (Revista do Colóquio, 2024)
In this essay, we present some aspects of the landscape observed by the visual artist, Hugo Bernardino Rodrigues, during his journeys between the sea and the mountains of Espírito Santo, with the aim of generating a visual/physical/memorial framework, and therefore, providing various studies for its technical and poetic development. It is considered that the apprehension of these landscapes influences their imagination, as well as their respective creative process.
Keywords: landscape; poetic; topophilia; Umwelt